Clojure for the brave and true : learn the ultimate language and become a better programmer - Higginbotham, Daniel, ....- (San Francisco : No Starch Press, 2015)
"Guide to the functional programming language Clojure. Teaches tools and techniques for writing programs in Clojure. Covers how to wield and compose Clojure's core functions; use Emacs for Clojure development; write macros to modify the Clojure programming language; and use Clojure's tools to simplify concurrency and parallel programming"--
Includes index.
Keywords: Clojure (Computer program language).